Observational study of tidal mixing asymmetry and eddy viscosity-shear covariance - induced residual flow in the Jiulong River estuary. (15th January 2020) - Cheng, Peng; Yu, Fengling; Chen, Nengwang; Wang, Aijun
Abstract: An observation study was conducted at three stations in the inner regime of the Jiulong River estuary to examine the tidal mixing asymmetry and its associated residual flow induced by eddy viscosity-shear covariance (ESCO). The water columns at the observation stations were approximately well-mixed during the later flood and were stratified during the early ebb, a typical tidal mixing asymmetry. Corresponding to the tidal variation of stratification, the Reynolds stress and vertical eddy viscosity, which were obtained using the ADCP variance method, exhibited distinct differences in the magnitude and vertical structure between flood and ebb tides. The ESCO flow was calculated using the decomposition method for estuarine circulation, revealing a two-layer vertical structure similar to density-driven flow but with a much greater magnitude, confirming the findings of previous generic model studies that the ESCO flow dominates the density-driven flow in periodically stratified estuaries. The drivers of tidal mixing asymmetry were explored using the potential energy anomaly method. Longitudinal straining reduced stratification during flood tides and reinforced stratification during ebb tides, whereas longitudinal advection acted in the opposite manner. Although the contribution of lateral circulation to stratification was neglected due to the lack of lateral observation data, scaling analysis revealed that lateral advection was important in the longitudinal dynamics and tidal evolution of stratification and warrants further study. Highlights: Observations showed that the inner regime of the Jiulong River estuary exhibited typical tidal mixing asymmetry. Longitudinal straining is the main driver of tidal mixing asymmetry whereas longitudinal advection acted in an opposite waymanner. The ESCO flow has a similar pattern as that of the gravitational circulation but with a much larger magnitude. The ADCP variance method is only reliable for homogeneous or weakly stratified flows.